Comparison of Treatment Outcomes Between Lesbian, Gay, Bisexual and Heterosexual Individuals Receiving a Primary Care Psychological Intervention. Issue 3 (5th October 2017) - Rimes, Katharine A.; Broadbent, Matthew; Holden, Rachel; Rahman, Qazi; Hambrook, David; Hatch, Stephani L.; Wingrove, Janet
Abstract : Background: Lesbian, gay and bisexual individuals experience more anxiety and depression than heterosexual people. Little is known about their comparative treatment response to psychological interventions.Aims: To compare sociodemographic/clinical characteristics and treatment outcomes across sexual orientation groups, for adults receiving primary care psychological interventions from Improving Access to Psychological Therapies (IAPT) services in London, adjusting for possible confounders.Method: Data from 188 lesbian women, 222 bisexual women, 6637 heterosexual women, 645 gay men, 75 bisexual men and 3024 heterosexual men were analysed from pre-treatment and last treatment sessions. Males and females were analysed separately.Results: Before treatment, lesbian and bisexual women were more likely to report clinical levels of impairment (Work and Social Adjustment Scale) than heterosexual women; there were no significant differences in depression (PHQ-9) or anxiety (GAD-7). Bisexual men were more likely to meet depression caseness than gay men but less likely to meet anxiety caseness than gay or heterosexual men. Compared with heterosexual women, lesbian and bisexual individuals showed smaller reductions in depression and impairment, controlling for age, ethnicity, employment, baseline symptoms, number of sessions and intervention type. Bisexual women experienced significantly smaller reductions in anxiety than heterosexual women and were less likely to show recovery or reliable recovery. There were no significant differences in treatment outcomes between gay, bisexual and heterosexual men.Conclusions: Reasons for poorer outcomes in lesbian and bisexual women require investigation, for example lifetime trauma or stigma/discrimination regarding gender or sexual orientation in everyday life or within therapy services.